Revisión y descripción de los principales candidatos vacunales útiles al propósito de desarrollar inmunidad contra el SARS-CoV-2 : avances y desafíos (2020)
SARS-CoV-2 is described as the etiological agent of COVID-19, an infectious pathology, whose most frequent symptoms are fever, myalgia, cough, and pulmonary affections. Considered by the WHO as responsible for the current pandemic. As the number of cases grows, COVID-19 has become a permanent threat to both health services and the world economy, therefore developing a safe and effective vaccine in the shortest possible time, has been a great challenge. This monograph seeks to synthesize the information found to date regarding the development of vaccines, analyze it to know the current situation of this disease, and present the advances, achievements, and challenges to be faced in the race to control this new emerging agent.